Smoking in outdoor areas of bars and cafés: Large differences between midday and evening prevalences. (December 2014) - Chan, Jacky; Burnett, Tristan; Baillie, Ranui; Blomfield, Sophia; Cameron-Christie, Peter; Dickson, James; Fleishl, William; Ghandi, Swetaa; Gordon, Katherine; Heo, Jaewon; Kesy, Agata; Kao, Alex Yu; et al.
<x xml:space="preserve">Abstract</x> Aim: There have been only two studies of the smoking prevalence outside bars/cafés worldwide, both undertaken in Australia. The aim of this study was to further develop the assessment of the prevalence of smoking outside bars/cafés in a busy urban area. It is important for smokefree places policymaking to have baseline data on smoking visibility at these places, so as to be able to gauge the effects of policy changes that may alter levels of smoking. Methods: Researchers observed smoking during eight 15-minute periods (during 12–1 pm and 7–8 pm) in April 2013 at 14 bar/café locations in central Wellington, New Zealand. Results: Of 2600 people observed in the outdoor areas of bars/cafés, 15.8% were observed smoking (95% confidence interval (CI): 14.5%–17.5%); 18.5% in the evening (95% CI: 16.8%–20.4%) compared to 9.1% at midday (95% CI: 7.2%–11.4%). Conclusion: Smoking was observed in the outdoor areas of the bars/cafés at a prevalence of double that found in the previous Australian studies. This may be accounted for by observation method or observation times, or may be due to a much wider range of premises in the Australian cities with outdoor areas, which are open later, or a much wider variety of patrons who used such areas, compared to in Wellington. We found twice the prevalence of smoking outside bars/cafés in evenings compared to midday. Such differences may be related to a greater consumption of alcohol in evenings or to a different patronage then. Smokefree policies covering these settings could help denormalize smoking.